The relationship of agility with women's football playing skills - Galih Pamungkas; Komarudin Komarudin; Saryono Saryono; Muhamad Ichsan Sabillah (Jorpres (Jurnal Olahraga Prestasi), 2023)
This study aims to test the relationship of agility with women's football playing skills. Methods used correlational research. The study was carried out on the players of Putri Mataram Sleman with a total sample of 20 players and an average age of 15-20 years. Players perform exercises with a frequency of 3 times a week. The instrument used to measure the agility of the Mataram Women's Player is the Illinois Agility Test with a validity of 0.87. Football skills ability using David Lee development test. Based on the statistical analysis of the normality test that has been carried out using the Shapiro-Wilk Test, the significance value is 0.085 0.05 which means that the data is normally distributed. In this study the correlation value obtained was 0.964. It can be concluded that there is a relationship between agility and football playing skills since the significance value is 0.964 0.05. Based on research conducted by researchers, it was found that agility correlates with the football playing skills of the Princess Mataram Sleman player.